2008
DOI: 10.1094/cchem-85-3-0379
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Acid and Alkali on Mechanical Properties of Compression‐Molded Gluten Bioplastics

Abstract: The present work was focused on the effects of acid and alkali on the uniaxial extensional deformation of gluten bioplastics compression‐molded at 80 and 110°C. Water absorption and morphology observation were also performed to characterize the properties and morphology of the gluten bioplastics. The results show that HCl did not show catalysis function for cross‐linking proteins at 80°C and even hindered the cross‐linking reaction at 110°C. On the other hand, NaOH generally accelerated the cross‐linking react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…12,13 Alkaline conditions affect cross-linking and the mechanical properties of gluten rubbers obtained by compression molding. 14,15 Zhang et al 14 reported an improved Young's modulus, tensile strength, and strain at break for gluten rubbers molded in the presence of added base and attributed these effects to cross-linking. However, the importance of alkaline treatment and, hence, the resulting nondisulfide bonds relative to that of disulfide bonds for the material properties of glassy gluten bioplastic is not yet known.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Alkaline conditions affect cross-linking and the mechanical properties of gluten rubbers obtained by compression molding. 14,15 Zhang et al 14 reported an improved Young's modulus, tensile strength, and strain at break for gluten rubbers molded in the presence of added base and attributed these effects to cross-linking. However, the importance of alkaline treatment and, hence, the resulting nondisulfide bonds relative to that of disulfide bonds for the material properties of glassy gluten bioplastic is not yet known.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Disulfide bonds are the predominant gluten cross-links, but at molding temperatures exceeding 130 °C also the dehydroalanine (DHA)-derived cross-link lanthionine (LAN) has been detected . Such cross-links are typically formed during heat and alkaline treatment of proteins. , Alkaline conditions affect cross-linking and the mechanical properties of gluten rubbers obtained by compression molding. , Zhang et al reported an improved Young’s modulus, tensile strength, and strain at break for gluten rubbers molded in the presence of added base and attributed these effects to cross-linking. However, the importance of alkaline treatment and, hence, the resulting nondisulfide bonds relative to that of disulfide bonds for the material properties of glassy gluten bioplastic is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…NaOH generally accelerates the cross-linking reaction, thus significantly improving Young's modulus, tensile strength, and strain at break. However, an NaOH content >0.5 wt% could cause adverse effects at moulding temperatures as high as 110°C [30]. Jansens et al [29] reported that alkaline conditions may induce protein degradation, likely caused by peptide bond hydrolysis, with the formation of low M W protein fragments.…”
Section: Discussionmentioning
confidence: 99%